آليات الحجاج البلاغية في الحديث النبوي الشريف نماذج مختارة - شيحي, تواتي طليبة, عائشة زينب (University of El-oued, 2021)
يتناول هذا العمل موضوع آليات الحجاج البلاغية في الحديث النّبوي الشّريف، وذلك من خلال نماذج مختارة، ولهذه الآليات أهمية بالغة في الأبعاد الحجاجية الإقناعية؛ وقد اعتمد الرّسول  في إيصال رسالته الحجاجية الإقناعية على العديد من الآليات البلاغية، وهذه الأخيرة لها بعد حجاجي إقناعي له تأثير قوي في المتلقي. Summary: This work deals with the topic of the rhetorical mechanisms of the argument in the noble hadith of the prophet, through selected models. These mechanisms have a great important in the persuasive argumentation dimensions. The prophet peace be upon him relied on many rhetorical mechanisms in delivering his message. This latter has a strong persuasive influence on the percipient.
Keywords: الحجاج البلاغة الحديث النبوي